Structural, magnetic and electrical properties of YBCO-123 superconductor reacted with Y₂O₃ and BaZrO₃ nanoparticles - Mohd Hapipi, Nurhidayah (2017)
In this work, superconducting properties of YBa2Cu3O7-δ (Y-123) reacted with 5.0 mol.% of Y2O3 and different molar percentages (mol.%) of BaZrO3 (BZO) nanoparticles were studied. Series 1 samples are Y-123 reacted with x mol.% BZO nanoparticles and Series 2 samples are Y-123 reacted with 5.0 mol.% of Y2O3 and x mol.% BZO nanoparticles (x = 0.0 – 7.0 mol.%). The samples were prepared using co-precipitation (COP) method. The phase formation, microstructure, magnetic and electrical properties of the samples were investigated using thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), temperature dependence of resistance measurement, and alternating current susceptibility (ACS). XRD patterns indicated that all of the samples could be indexed to space group (Pmmm) with orthorhombic crystal structure. Y-123 is the major phase while Y-211 was detected as minor secondary phase in all the samples. Besides, BZO peaks started to appear when its addition level was increased from 1.0 mol.%. The SEM images showed that all the samples have irregular shaped grains and they are randomly distributed. The average grains size for both series increased in the range of 0.30 μm to 0.50 μm with increasing amount of BZO nanoparticles addition. Yet, the grain size for Series 2 samples is slightly higher than that in Series 1 indicating that Y2O3 may promote grain growth. The temperature dependence of resistance measurements showed a metallic behaviour at normal state and a superconducting transition to zero resistance for all the samples. The value of Tc for the pure sample is 91.6 K and it decreased to 81.5 K and 87.6 K for Series 1 and Series 2 samples, respectively for 7.0 mol.% BZO addition. The Tc values and the transition width, ΔTc for the Series 2 are slightly higher than Series 1. The higher value of transition width, ΔTc shows the degradation of homogeneity within the samples. The ACS measurement showed the decreasing of Tc-onset, Tcj and Tp with the increase of BZO nanoparticles addition for all the samples. The decrease of Tcj and Tp is due to the weakening of the intergranular coupling and the decrease of pinning forces. The obtained Io and Jcm for Series 2 are higher than that for Series 1 indicating that the grain coupling of the former is stronger. As a conclusion, the results shows that the coaddition of Y2O3 and BZO (Series 2) can maximize the Jcm value and improve a flux pinning if compared to the addition of BZO only (Series 1). However, the optimum value for co-addition of BZO is only up to 2.0 mol.% since further addition will degrade the superconductivity of the samples. The highest Jcm is 2.096 A/ cm2 for co-addition of 2.0 mol.% BZO and Y2O3.